Patients Undergoing Manipulation under Anesthesia following Primary Total Knee Arthroplasty: Are Their Patient-Reported Outcome Measures Inferior? - Sirignano, Michael N.; Rowe, Robert S.; Gainer, James C.; Royster, Brett W.; Smith, Langan S.; Altman, Kyle M.; Yakkanti, Madhusudhan R.; Malkani, Arthur L. (The Journal of Knee Surgery, 2025)
Stiffness after total knee arthroplasty (TKA) can lead to decreased function and patient dissatisfaction. Manipulation under anesthesia (MUA) is often performed to improve range of motion (ROM); however, there is no consensus on indications or timing. The purpose of this study was to compare clinical results and patient-reported outcome measures (PROMs) between patients who underwent MUA versus those with an uncomplicated postoperative course following primary TKA. This was an institutional review board-approved retrospective review of 116 consecutive patients who underwent MUA from 2013 to 2019 following primary TKA due to stiffness. Indication for MUA was failure to achieve 105 degrees of knee flexion at 6 weeks following surgery. Five patients underwent revision surgery and 15 patients from the MUA group were excluded: 12 lost to follow-up and 3 deaths. The remaining 96 MUA patients were matched to 288 TKAs who did not require MUA or revision, all with a minimum 2-year follow-up. Patients who underwent MUA were younger (60.7 vs. 66.3 years, p < 0.001) and had less preoperative knee flexion (105.4 vs. 110.7 degrees, p < 0.001). There were five (4.9%) revisions in the MUA group: two instability, two chronic pain, and one arthrofibrosis. There were no differences between the groups with respect to postoperative Knee Society Knee Score, Western Ontario and McMaster Universities Osteoarthritis, Knee Injury and Osteoarthritis Outcome Score for Joint Replacement, Forgotten Joint Score-12, satisfaction, or complications. Satisfaction rates were 88.5% among MUA patients and 89.6% among non-MUA patients (p = 1.0). Patients undergoing MUA following TKA, using the criteria of failure to achieve 105 degrees of flexion by 6 weeks postoperatively, were able to achieve similar PROMs and satisfaction compared with a control group with a low incidence of revision due to persistent arthrofibrosis.
Keywords: total knee arthroplasty; manipulation under anesthesia; range of motion; patient-reported outcome measures; satisfaction